Targeted next-generation sequencing of candidate regions identified by GWAS revealed SNPs associated with IBD in GSDs - Peiravan, Atiyeh; Salavati, Mazdak; Psifidi, Androniki; Sharman, Mellora; Kent, Andrew; Watson, Penny; Allenspach, Karin; Werling, Dirk (Frontiers in Veterinary Science, 2025)
Canine Inflammatory bowel disease (IBD) is a chronic multifactorial disease, resulting from complex interactions between the intestinal immune system, microbiota and environmental factors in genetically predisposed dogs. Previously, we identified several single nucleotide polymorphisms (SNP) and regions on chromosomes (Chr) 7, 9, 11 and 13 associated with IBD in German shepherd dogs (GSD) using GWAS and FST association analyses. Here, building on our previous results, we performed a targeted next-generation sequencing (NGS) of a two Mb region on Chr 9 and 11 that included 14 of the newly identified candidate genes, to identify potential functional SNPs that could explain these association signals. Furthermore, correlations between genotype and treatment response were estimated. Results revealed several SNPs in the genes for canine EEF1A1, MDH2, IL3, IL4, IL13 and PDLIM. Based on the known function of their human orthologues, these results further our insight into their potential contribution to the pathogenesis of IBD in dogs. In addition, several pathways involved in innate and adaptive immunity and inflammatory responses (i.e., T helper cell differentiation, Th1 and Th2 activation pathway, communication between innate and adaptive immune cells and differential regulation of cytokine production in intestinal epithelial cells by IL-17A and IL-17F), were constructed involving the gene products in the candidate regions for IBD susceptibility. Interestingly, some of the identified SNPs were present in only one outcome group, suggesting that different genetic factors are involved in the pathogenesis of IBD in different treatment response groups. This also highlights potential genetic markers to predict the response in dogs treated for IBD.